Allometric relationships among tree-size variables under tropical forest stages in Gia Lai, Vietnam - Bui, Manh Hung; Phung, Van Khoa; Nguyen, Thi Bich Phuong; Nguyen, Van Quy; Dell, Bernard (Ecological Questions, 2022)
Allometric models play an undeniable role for estimating hard-to-measure quantities such as volume, biomass and carbon stock in forests. However, so far there has been limited model development for native forests in Vietnam. Therefore, this study was conducted to build and analyze the effectiveness of nonlinear and mixed models for secondary and old-growth forests in Gia Lai, Vietnam. The study measured diameter at breast height, total height, commercial height and crown width of forest trees in 20 plots (10 plots for each forest stage). The results showed that diameter had the strongest relationship with height. In the secondary forest, the Power, Korf and Ratskowky models were the best for pairs of variables, while Prodan, Weibull and Power models were the best fit in the old-growth forest. The nonlinear mixed-effect models were better than classic nonlinear models in both forest stages. Fixed and mixed models developed in this study are very valuable for estimating difficult-to-measure quantities and contribute to effective forest management in the study region.